2018
DOI: 10.1055/a-0658-1389
|View full text |Cite
|
Sign up to set email alerts
|

Large adrenal cyst masquerading as a pancreatic cystic tumor: a rare diagnosis based on endoscopic ultrasound

Abstract: Adrenal cystic lesions constitute a rare finding and usually are diagnosed incidentally as retroperitoneal cysts during imaging studies. A major issue, especially for the large-sized ones, is their preoperative diagnosis and management, as imaging modalities often fail to detect their exact origin prior to surgery. We report a case of a big adrenal cyst that was mistakenly diagnosed and followed up as pancreatic cystic tail tumor. Our thorough workup, which included endoscopic ultrasound (EUS), managed to deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…In some cases, this can lead to misdiagnosis when imaging fails to determine the origin of retroperitoneal tumors; therefore, are diagnosed during surgery. A similar case was reported in a 47-year-old patient with a large adrenal cyst misdiagnosed and followed up as pancreatic cystic tumor [ 10 ]. Another study reported a case of a giant adrenal cyst diagnosed during surgery [ 8 ].…”
Section: Discussionsupporting
confidence: 58%
“…In some cases, this can lead to misdiagnosis when imaging fails to determine the origin of retroperitoneal tumors; therefore, are diagnosed during surgery. A similar case was reported in a 47-year-old patient with a large adrenal cyst misdiagnosed and followed up as pancreatic cystic tumor [ 10 ]. Another study reported a case of a giant adrenal cyst diagnosed during surgery [ 8 ].…”
Section: Discussionsupporting
confidence: 58%
“…A similar clinical situation was described by Korean authors [66]. Extrapancreatic cysts, such as tumors and duplication cysts of the stomach [67], tumors of the left adrenal gland [68], tumors of the spleen [69,70] can imitate pancreatic cysts. In rare cases, echinococcal cysts of the pancreas are found [71].…”
Section: Rare Pancreatic Cystssupporting
confidence: 66%